Selecting regional information for government planning and decision-making - Hirsch, Werner Z.; Sonenblum, Sidney; California (New York : Published in cooperation with the Institute of Government and Public Affairs, University of California, Los Angeles [by] Praeger Publishers, 1970)
The purpose of this study is to develop a sun-national information design (SID) that will facilitate improved decisions at the state and local levels
Includes bibliographical references.
sju 22/01/2019
Loans
Keywords: Economic policy; Decision making; Information storage and retrieval systems